2013
DOI: 10.2174/09298673113209990147
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Peptides: Trends and Perspectives for Future Research

Abstract: In recent years, much attention has been given to dietary antioxidants, especially polyphenols. Several peptides derived from protein molecules have also been found to show antioxidant capacity along with other biological properties and thus there is an increasing interest in these compounds as health promoters. This review summarizes and discusses the main sources of antioxidative peptides with focus on food-derived peptides (animal, plant and marine sources), methods of preparation, antioxidant capacity eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 120 publications
0
30
0
Order By: Relevance
“…This enables access to scavenge free radicals generated at the lipid phase (Freitas, Andrade, Silva, Rocha-Santos, Duarte, & Gomes, 2013;Ko et al, 2012;Ranathunga, Rajapakse, & Kim, 2006). Some of the peptides obtained through the hydrolysis of cattle plasma in this study appear to be unique compared to other reported antioxidant peptides.…”
Section: Identification Of Peptides Within Rp-hplc Fractionmentioning
confidence: 87%
“…This enables access to scavenge free radicals generated at the lipid phase (Freitas, Andrade, Silva, Rocha-Santos, Duarte, & Gomes, 2013;Ko et al, 2012;Ranathunga, Rajapakse, & Kim, 2006). Some of the peptides obtained through the hydrolysis of cattle plasma in this study appear to be unique compared to other reported antioxidant peptides.…”
Section: Identification Of Peptides Within Rp-hplc Fractionmentioning
confidence: 87%
“…In a previously published review by Freitas et al [43] these same amino acids were, together with the sulfur containing amino acids, reported to provide antioxidant activity. All of the brines tested here contained these amino acids (Table 4).…”
Section: Antioxidant Activity In the Brinesmentioning
confidence: 93%
“…The three tested antioxidant activities can, according to different mechanisms, prevent oxidation in food. Nevertheless, the classic in vitro tests for measuring antioxidant activity may not reveal the exact antioxidant potential of the brines in foods, and thus, tests in different food matrices should also be conducted [43]. Based on Figures 2-4, the most promising brines for further testing the antioxidant activity is the two blood-rich brines, TSa and TSp, together with SC and future studies will reveal whether the activity is solely in the protein-free fraction or if protein/peptides contribute to their antioxidant activity.…”
Section: Antioxidant Activity In the Brinesmentioning
confidence: 99%
“…Hu et al [37] found diterpene erythrazole B in active extracts of Erythrobacter sp., and this compound showed citotoxic properties against non-small-cell lung cancer (NSCLC) cell lines. Tsukada et al [44] isolated the decarboxyhydroxycitrinone, a terpene, from the marine fungus Arthrinium sacchari, with antiangiogenic activity.…”
Section: Terpenesmentioning
confidence: 99%